A vegetarian diet does not protect against nonalcoholic fatty liver disease (NAFLD): A cross-sectional study between Buddhist priests and the general population - Choi, Sung Hun; Oh, Dong Jun; Kwon, Ki Hwan; Lee, Jun Kyu; Koh, Moon-Soo; Lee, Jin Ho; Kang, Hyoun Woo (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: There is limited data that supports a role for a vegetarian diet in nonalcoholic fatty liver disease (NAFLD). The aim of this study is to evaluate the relationship between vegetarian diets and NAFLD, considering metabolic syndrome and obesity. Materials and Methods: This is a cross-sectional, retrospective study comparing the prevalence of NAFLD of 615 Buddhist priests and age-, sex-, Body mass index (BMI)-and presence/absence of metabolic syndrome-matched controls who underwent routine health checkups in a health promotion center. Diagnosis and severity of NAFLD was determined based on ultrasonographic findings. Results: The prevalence of NAFLD was not statistically significantly different between the Buddhist priests and the general population (29.9% vs. 25.05%, p=0.055). The Buddhist priest group had higher serum albumin, serum aspartate aminotransferase (AST), serum alanine aminotransferase (ALT), and serum triglyceride levels and lower serum total bilirubin, serum fasting glucose, and serum high density lipoprotein (HDL) levels than the general population group. In univariate analysis and multivariate analysis, NAFLD was associated with old age, male gender, increased BMI, increased waist circumference, metabolic syndrome, high albumin, high glucose, high AST, high ALT, high gamma glutamyl transpeptidase (GGT), high triglycerides, low HDL, high low density lipoprotein (LDL), and high total cholesterol. Conclusion: The vegetarian diet does not protect against NAFLD.